Sales-discount regulation : how much bazaar do consumers want? - Evelyn Korn (Philipps-Universität Marburg, Fachbereich Wirtschaftswissenschaften, 2007)
In July 2001 the 70-year-old German Rabattgesetz that prevented negotiations in retail business has been abolished. During the abolition process consumer- as well as retailer pressure groups claimed that significant damages for their clients were to be expected. Using game theoretic modelling this paper discusses which economic consequences could arise from the amendment. It shows that none of the abovementioned fears were justified. In addition, it uses a revealed-preference argument based on these predictions and on data concerning the dissemination of customer cards to describe consumers' general attitudes towards bargaining.
Keywords: 330